Evaluasi Cemaran Bakteri Escherichia coli dan Coliform pada Air Minum Isi Ulang di Kecamatan Patrang, Jember - Alisyah Pratiwi; Hartalina Mufidah; Rian Anggia Destiawan (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Water plays a fundamental role in sustaining human life, particularly as a source of drinking water. Nonetheless, the consumption of water that does not comply with established health standards can result in illnesses such as diarrhea and vomiting. In the Patrang District, the use of refillable drinking water has gained popularity as an economical substitute for bottled water. Despite its convenience, there are growing concerns about the microbiological safety of refillable drinking water, especially regarding contamination by Coliform and Escherichia coli bacteria, which serve as key indicators of water hygiene and safety. The objective of this research was to determine the contamination levels of Coliform and Escherichia coli bacteria in refillable drinking water. The study utilized a quantitative research design with descriptive analysis and employed the Most Probable Number (MPN) method for testing. Data collection took place from May to June 2024, comprising five water samples labeled X, Y, Z, A, and B, obtained from refillable drinking water depots in Patrang District using a simple random sampling approach. The results indicated that out of the five samples tested, the sample labeled Z was positive for Coliform with an MPN value of 920 cfu/mL, while the sample labeled A was positive for both Coliform and Escherichia coli with an MPN value of 2,000 cfu/mL. From these findings, two samples (Z and A) were identified as contaminated, with the highest bacterial concentration found in sample A, which had an MPN value of 2,000 cfu/mL